Corrosion Protection and Surface Treatment of Magnesium Alloys Used for Orthopedic Applications - Nabil Nassif; Ibrahim Ghayad (Advances in Materials Science and Engineering)
An overview is reported about the history of prevailing magnesium alloys as orthopedic biodegradable materials. Important features of the effect of alloying additions, along with surface treatments for corrosion protection of magnesium alloys, are described. Hydroxyapatite (HA), the promising coat deposited by different direct and electrochemical methods to tailor corrosion resistance and biocompatibility, is discussed. Surface modifications, such as microarc oxidation or anodization which lead to nanostructures fabricated to provide better adhesion for HA coatings, are presented.